2008
DOI: 10.1007/s00259-008-0984-x
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of the effects of chemotherapy with longitudinal FDG small-animal PET in human testicular cancer xenografts: early flare response does not reflect refractory disease

Abstract: FDG PET may be useful in the early evaluation of treatment in patients with testicular cancer. In our model, a very early increased [(18)F]-FDG uptake was related to a transient cell cycle arrest and early stage apoptosis but did not reveal refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…increase in tumor FDG uptake was observed during the first week after chemotherapy, independent of tumor growth. This observation was followed by a rapid decrease in FDG uptake and subsequent tumor regression (39)(40)(41). The cause of the observed flare was uncertain; it was hypothesized that exposure to chemotherapy transiently induced glucose hypermetabolism in tumors, and cancer cells, inefficiently adapted to the induced metabolic stress, underwent apoptotic cell death through metabolic catastrophe (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…increase in tumor FDG uptake was observed during the first week after chemotherapy, independent of tumor growth. This observation was followed by a rapid decrease in FDG uptake and subsequent tumor regression (39)(40)(41). The cause of the observed flare was uncertain; it was hypothesized that exposure to chemotherapy transiently induced glucose hypermetabolism in tumors, and cancer cells, inefficiently adapted to the induced metabolic stress, underwent apoptotic cell death through metabolic catastrophe (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging has been shown to be particularly useful for evaluating the efficacy of molecularly targeted therapies given either alone or in combination with conventional chemotherapies in preclinical studies (9,10). In clinical trials, PET can predict metabolic changes before tumor shrinkage, at a time when conventional imaging modalities and conventional criteria of evaluation (the criteria of the World Health Organization or the response evaluation criteria in solid tumors) are ineffective (11).…”
mentioning
confidence: 99%
“…Several positron emission tomography (PET) studies have been reported in mouse models of human cancer (16,17). The most frequently employed radiotracer was 18 (19,20).…”
Section: Introductionmentioning
confidence: 99%